Oxidation characteristics and electrical properties of La- or Ce-doped MnCo2O4 as protective layer on SUS441 for metallic interconnects in solid oxide fuel cells. (21st April 2020) - Tseng, Hui-Ping; Yung, Tung-Yuan; Liu, Chien-Kuo; Cheng, Yung-Neng; Lee, Ruey-Yi
Abstract: In this study, we discuss the evolution of area specific resistance (ASR) of SUS441 which was coated with MnCo2 O4, La-doped MnCo2 O4, and Ce-doped MnCo2 O4, respectively. These systems are meant to simulate as protective layers for metallic interconnects in solid oxide fuel cells (SOFCs) and were tested at 800 °C in 2 L/min air flow for 5600 h. The protective coatings were deposited by using pulsed DC magnetron sputtering and the thickness was 5.0 ± 1.0 μm. The compositions and microstructures were observed by SEM/EDS and XRD. Results show that a trace amount of La addition into MnCo2 O4 is beneficial to keep stable electrical resistance and inhibit the growth of the oxide scale between the SUS441 substrate and the protective layer for this coating system. However, visible cracks can be seen in MnCo2 O4 and Ce-doped MnCo2 O4 specimens at the interfacial layer between the oxidation scale on SUS441 and the coatings after heat treatment at elevated temperatures. Highlights: The oxide scale without spallation and thinning by La-doped MCO. Porosity of MCO decreased by La or Ce additions. La-MCO lowers the increasing rate of ASR values.